2009
DOI: 10.1016/j.envres.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of polychlorinated aromatic hydrocarbons in serum in three age classes—Methodological implications for human biomonitoring

Abstract: a b s t r a c tHuman biomonitoring provides an integrated measure for individual exposure to environmental pollutants. Better insight in inter-individual variability of biomarkers of exposure may help in the interpretation of biomonitoring studies.The aim was to study the impact of outliers, determine the optimal unit for fat-soluble biomarkers in serum and quantify the major determinants for biomarkers of exposure to polychlorinated aromatic hydrocarbons (PCAHs) in three age groups.Data were obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
5
14
1
Order By: Relevance
“…Consistent with other studies of persistent organic pollutants in this cohort and other populations (Burns et al 2009; Den Hond et al 2009; Gallo et al 2011; Humblet et al 2010; Karmaus et al 2001), lower BMI predicted higher serum OCP concentrations. This finding may be attributable to a smaller volume of distribution in boys with lower BMI, resulting in higher serum concentrations (Wolff et al 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with other studies of persistent organic pollutants in this cohort and other populations (Burns et al 2009; Den Hond et al 2009; Gallo et al 2011; Humblet et al 2010; Karmaus et al 2001), lower BMI predicted higher serum OCP concentrations. This finding may be attributable to a smaller volume of distribution in boys with lower BMI, resulting in higher serum concentrations (Wolff et al 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies (Barr et al 2006; Den Hond et al 2009; Gallo et al 2011; Karmaus et al 2001), longer breastfeeding duration (> 13 weeks) predicted higher OCP concentrations. Although breastfeeding in our cohort ended years before OCP measurement, childhood concentrations of lipophilic compounds track closely with breastfeeding exposure in infancy (Patandin et al 1999).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Den Hond et al (2009), conclude that in terms of adjusted R 2 , the regression model with TSL-corrected OCs was superior to models with TSL-uncorrected OCs. In previous articles we concluded that correcting OCs by TSL may be inappropriate in patients with severe diseases as pancreatic cancer (Porta et al, 2009a).…”
Section: Discussionmentioning
confidence: 79%